International consensus statement on injury and illness reporting in professional road cycling. Issue 2 (3rd April 2021) - Heron, Neil; Sarriegui, Inigo; Jones, Nigel; Nolan, Rory
ABSTRACT: Introduction: Road cycling is a very common recreational and elite sport. To facilitate consistent reporting of injuries and illness in professional road cycling we want to establish terms, definitions, and methods for injury and illness reporting in elite road cycling epidemiology studies, similar to other sports. Aims/objectives: The aim of this study is to establish an international expert statement for injury and illness reporting in professional road cycling. Methods: We initially conducted a literature review of the injury and illness epidemiology studies in sport and identified popular terms, definitions, and methods which could be applied to road cycling. These terms were then reviewed by our expert panel, with clarification of terms and definitions and additional terms added, if required. The final consensus statement was then agreed by all authors. Results: The relevant definitions for use in professional road cycling epidemiology studies have been agreed. Injury rates should be reported as per 1, 000 hours of cycling training, both in and outdoors, and per 1, 000 hours of competition as well as per 1, 000 hours of non-cycling training. Discussion: We encourage authors to use this expert paper when undertaking injury and illness epidemiology studies in professional road cycling to increase the rigor of the studies as well as allowing comparability between different road cycling studies and epidemiology studies in other sports.